Cost and Cost Savings of Navigation Services to Avoid Rehospitalization for a Comorbid Substance Use Disorder Population. Issue 8 (10th August 2022) - Orme, Stephen; Zarkin, Gary A.; Dunlap, Laura J.; Nordeck, Courtney D.; Schwartz, Robert P.; Mitchell, Shannon G.; Welsh, Christopher; O'Grady, Kevin E.; Gryczynski, Jan
Abstract : Background: A randomized clinical trial found that patient navigation for hospital patients with comorbid substance use disorders (SUDs) reduced emergency department (ED) and inpatient hospital utilization compared with treatment-as-usual. Objective: To compare the cost and calculate any cost savings from the Navigation Services to Avoid Rehospitalization (NavSTAR) intervention over treatment-as-usual. Research Design: This study calculates activity-based costs from the health care providers and uses a net benefits approach to calculate the cost savings generated from NavSTAR. NavSTAR provided patient navigation focused on engagement in SUD treatment, starting before hospital discharge and continuing for up to 3 months postdischarge. Subjects: Adult hospitalized medical/surgical patients with comorbid SUD for opioids, cocaine, and/or alcohol. Cost Measures: Cost of the 3-month NavSTAR patient navigation intervention and the cost of all inpatient days and ED visits over a 12-month period. Results of Base Case Analysis: NavSTAR generated 17, 780 per participant in cost savings. Ninety-seven percent of bootstrapped samples generated positive cost savings, and our sensitivity analyses did not change our results. Limitations: Participants were recruited at one hospital in Baltimore, MD through the hospital's addiction consultation service. Findings may not generalize to the broader population. Outpatient health care cost data was not available through administrative records. Conclusion: Our findings show that patient navigation interventions should be considered by payors and policy makers to reduce the high hospital costs associated with comorbid SUD patients.